Meteorological conditions of extreme avalanche formation in the Caucasus Mountains (according to observations and reanalysis) - N. E. Kuksova; P. A. Toropov; A. D. Oleinikov (Лëд и снег, 2021)
The possibility of using the data of modern ERA-Interim, CFSR and NCEP-NCAR re-analyses to assess an avalanche danger in the mountains of the North Caucasus is considered. Previously, the mean seasonal values of the surface air temperature and seasonal precipitation amounts obtained from the reanalysis archives were compared with the data of meteorological stations. The mean temperature of the cold period (November–March) was best reproduced by the ERA-Interim reanalysis: the correlation coefficients amounted to 0.8–0.9, and the average deviation from the station data ±1.7 °C. The accuracy of measurements of precipitation is lower, but the magnitude of the errors does not exceed the limits of inter-seasonal variability. To estimate the avalanche hazard, a correlation matrix was used based on the relationship of the avalanche hazard indicator with the standard deviations of seasonal values of temperature and precipitation. The ERA-Interim reanalysis reproduces the avalanche danger in the North Caucasus most adequately (71% of coincidences with the actually observed events). Synoptic processes which may promote formation of catastrophic avalanches in the North Caucasus were also determined. The most typical situation is the position of a high-level cyclone over the Eastern Europe, accompanied by the invasion of cold air masses from Scandinavia that activates cyclogenesis in the Mediterranean. It was found that the extreme avalanche hazards occurred at negative anomalies of mean seasonal air temperature near the ground and in the middle troposphere (about 1.5–2 °C) when the integral water content of the atmosphere was close to the norm.